DREAM-ICD-II Study. Issue 10 (16th December 2021) - Steinberg, Christian; Dognin, Nicolas; Sodhi, Amit; Champagne, Catherine; Staples, John A.; Champagne, Jean; Laksman, Zachary W.; Sarrazin, Jean-François; Bennett, Matthew T.; Plourde, Benoit; Deyell, Marc W.; Andrade, Jason G.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Regulatory authorities of most industrialized countries recommend 6 months of private driving restriction after implantation of a secondary prevention implantable cardioverter-defibrillator (ICD). These driving restrictions result in significant inconvenience and social implications. This study aimed to assess the incidence rate of appropriate device therapies in contemporary recipients of a secondary prevention ICD. Methods: This retrospective study at 3 Canadian tertiary care centers enrolled consecutive patients with new secondary prevention ICD implants between 2016 and 2020. Results: For a median of 760 days (324, 1190 days), 721 patients were followed up. The risk of recurrent ventricular arrhythmia was highest during the first 3 months after device insertion (34.4%) and decreased over time (10.6% between 3 and 6 months, 11.7% between 6 and 12 months). The corresponding incidence rate per 100 patient-days was 0.48 (95% CI, 0.35–0.64) at 90 days, 0.28 (95% CI, 0.17–0.45) at 180 days, and 0.21 (95% CI, 0.13–0.33) between 181 and 365 days after ICD insertion ( P <0.001). The cumulative incidence of arrhythmic syncope resulting in sudden cardiac incapacitation was 1.8% within the first 90 days and subsequently dropped to 0.4% between 91 and 180 days ( P <0.001) after ICD insertion. Conclusions: The incidence rate of appropriate therapies resulting in sudden cardiac incapacitation in contemporary recipients of a secondary prevention ICD is much lower than previously reported and declines significantly after the first 3 months. Lowering driving restrictions to 3 months after the index cardiac event seems safe, and revision of existing guidelines should be considered in countries still adhering to a 6-month period. Existing restrictions for private driving after implantation of a secondary prevention ICD should be reconsidered.